Analisis Sintaksis Teks "Mengurangi, Memakai Ulang, dan Mendaur Ulang Sampah" dalam Pembelajaran Bahasa Indonesia Kelas V SD - Widyawati, Widyawati; Nugraheni, Aninditya Sri; Lestari, Futry Ayu; Mujahida, Anni; Qubro, Nia Aulia Khodijatul (Jurnal Simki Pedagogia, 2026)
This study aims to analyze syntactic functions in explanatory texts entitled "Reduce, Reuse, and Recycle Waste" for Indonesian language learning in grade V elementary school, focusing on the identification of Subject elements, Predicates, Objects, Complements, and Descriptions (S-P-O-Pel-K). A literature study method with a qualitative descriptive approach is used, involving the analysis of qualitative content from primary texts and secondary sources such as articles, books, and relevant references. The results of the analysis showed variations in sentence structure, ranging from simple patterns (S-P-O, S-P-K) to complex (S-P-O-Pel, S-P-Pel-K, K-S-P-Pel), including fragment sentences (K-O) and compound elements, which supported the clear delivery of cause-and-effect relationships, definitions, and waste management goals. These findings strengthen syntactic understanding and linguistic literacy, although limited to a single text analysis. This research is expected to be a reference for educators to improve students' ability to recognize and compose sentences, as well as support environmental awareness at the elementary school level.